GREEN STRUCTURAL LIGHTWEIGHT CONCRETE UTILIZING MEDIUM-K BASALTIC ANDESITIC PUMICE AND SCORIA - Agoes Soehardjono; Hendro Suseno; I Nyoman Gede Wardana; Arief Rahmansyah (Journal of Environmental Engineering and Sustainable Technology, 2017)
ABSTRACTThis study presented observations of the suitability of medium-K basaltic andesitic pumice and scoria as a coarse aggregate on structural lightweight concrete that was environmental friendly and energy saving. Testing results indicated that this typical pumice and scoria fulfilled the requirements as a coarse lightweight aggregate. The mix design of specified compressive strengths yielded a lower proportion of Portland Pozzolan Cement (PPC) than previous studies. Testing results of fresh concrete showed a satisfactory workability at determined slump values without segregation and excessive bleeding. Testing results of hardened concrete showed that the density reduction was about 20 %, but there was a density of scoria lightweight concrete that exceeded slightly the requirements. All compressive strengths complied with the requirement but there was a pumice lightweight concrete that did not reach the specified compressive strength. The modulus of elasticity and splitting tensile strength were relatively low compared to normalweight concrete as control, whereas drying shrinkage was lower than in previous studies.KEYWORDS : green lightweight concrete, pumice, scoria, environmental friendly, energy saving.